Root traits mediate functional guilds of soil nematodes in an ex-arable field. (December 2020) - Zhang, Chongzhe; Wang, Jiajun; Ren, Zhuhong; Hu, Zhengkun; Tian, Shanyi; Fan, Wenqing; Chen, Xiaoyun; Griffiths, Bryan S.; Hu, Feng; Liu, Manqiang
Abstract: One of the greatest challenges in soil ecology is to disentangle the plant-mediated bottom-up factors regulating soil biodiversity and community composition. The soil food web, fundamentally driving nearly all ecosystem functions, is controlled by the quantity and quality of root-mediated resources. Here, a trait-based approach was adopted to explore the divergence of soil nematode functional guilds and their connections to root traits belonging to distinct plant resource-use strategies. Root traits and rhizosphere nematode functional guilds were measured on four plant species in an ex-arable field. Results showed that plant species exhibiting acquisitive strategies promoted nematode abundance in contrast to species with conservative strategies. Further, the results also supported that plant resource-use strategies could regulate nematode life strategies in a bottom-up manner. However, lower proportions of opportunist nematodes in rhizosphere were found in acquisitive plants rather than conservative plants, mainly attributed to the stronger top-down regulation as a dominant control within the former than the later ones. Structure equation modeling revealed that root length density could primarily modulate nematode abundance and functional guilds mainly through changes in nitrogen availability of rhizosphere, as indicated by mineral N and enzymatic stoichiometry. Overall, our findings extend the conceptual framework based on a trait-centred view spanning plants to the soil food web, and this knowledge is critical to understand the mechanisms of ecosystem process. Highlights: Acquisitive plants promoted nematode abundance and K-strategist nematodes. Conservative plants supported mainly r-strategist nematodes. Root length density was the key root trait for regulating soil nematodes.